Double inner standard plot model of an electrophoresis titration chip for a portable and green assay of protein content in milk. Issue 3 (2nd January 2019) - Wang, Cunhuai; Zhang, Qiang; Liu, Xiaoping; Li, Guoqing; Kong, Hao; Khan, Muhammad Idrees; Xiao, Hua; Wang, Yuxing; Liu, Weiwen; Cao, Chengxi
Abstract : High portability and environmental safety ("green") are two of the most important objectives pursued by microfluidic methods. Abstract : High portability and environmental safety ("green") are two of the most important objectives pursued by microfluidic methods. However, there remain many challenges for the design of portable and visual microfluidic methods ( e.g., chip electrophoresis) due to use of a cumbersome pump, power supply and detector. Herein, a facile double inner standard plot (DISP) model of electrophoresis titration (ET) was proposed for portable and visual assay of proteins in test milk samples without use of a pump, power supply or detector based on a moving reaction boundary (MRB) chip. The DISP-ET model predicted that: (i) by setting the upper limit (UL) and lower limit (LL) of double inner standard milk protein contents, points U and L were, respectively, achieved in the relationship D = − aC + b ( D : MRB motion distance; C : protein content); and (ii) the two points divided both the C -axis and D -axis into "poor", "eligible" and "superior" rulers scaled for quantitative assay of test samples. To demonstrate the model of DISP-ET, an original portable device (120 mm × 78 mm × 30 mm, 341 g) was designed, which had a chip (25 mm × 25 mm × 4 mm) of three channels (15 mm × 200 μm × 80 μm), platinum electrodes, a lithium cell and touch screen. A series of experiments were undertaken based on the developed portable device. The relevant experiments demonstrated systemically the validity of the DISP-ET model, theory and method. In particular, the experiments clearly showed the advantages of the DISP-ET chip: portability, visuality, green use, rapidity, and flexibility for real-life use. Finally, the device was applied for a portable and visual assay of fresh milk from a cow on a dairy farm. The DISP-ET model opens a window for designing portable and visual quantitative methods of food-safety control and clinical diagnoses.